دراسة هيدروجيوكيميائية للمياه الجوفية في المنطقة الواقعة بين نهري الصنوبر والكبير الشمالي - محمد, أحمد; حايك, شريف; راعي, كنان (Latakia University Journal -Basic Sciences Series, 2013)
يتضمن هذا البحث دراسة هيدروجيوكيميائية لبعض آبار المياه الجوفية المختارة من المنطقة الواقعة بين نهري الصنوبر والكبير الشمالي بهدف تحديد نوعية مياهها ومنشأ هذه المياه من أجل التخطيط المستقبلي الأمثل لاستعمالات الموارد المائية في هذه المنطقة. وقد تبين من خلال هذه الدراسة وجود نمطين هيدروكيميائيين أساسيين: الأول هيدروكربوناتي ـــــــ مغنيزي، كلسي، صودي للمياه، والثاني سولفاتي ـــــــ كلسي، مغنيزي، صودي، وهذه الأنماط الجيوكيميائية تشير إلى وجود عدد من الأملاح في المياه الجوفية تمّ حسابها إذ تبين تشكل ملحي كبريتات الصوديوم وهيدروكربونات الصوديوم واللذين يشيران إلى المنشأ الجوي الراشح للمياه (عميق وسطحي)، وملح كلور المغنيزيوم الذي يشير إلى المنشأ البحري، وأن المياه في كافة الآبار صالحة لأغراض الري. This research includes a Hydrogeochemical study of specific ground water wells between AL-Snobar and AL-Kabir AL-Shimali Rivers. This aims at specifying water quality and origion in order to plan the optimum future ways of using water supplies in the region. This study finds out two main hydrochemical types: a hydrocarbon type of water having a high content of magnesium, lime or sodium, and a sulpharic type of water having a high content of lime, magnesium or sodium. These two geochemical types show that a number of minerals can be found in groundwater such as Na2SO4 and NaHCO3 which indicates the air origin of filtrated water, and MgCl2 which indicates the sea origin. In addition, it indicates that groundwater in all wells can be used for irrigation.